The Use of Seasonal Climate Forecasting in Policymaking: Lessons from Northeast Brazil - Lemos, Maria Carmen; Finan, Timothy J.; Fox, Roger W.; Nelson, Donald R.; Tucker, Joanna (Climatic change, 2002)
This article examines the use of seasonal climate forecasting in public and private efforts to mitigate the impacts of drought in Ceara, Northeast Brazil. Here, forecasts have been directed towards small scale, rainfed agriculturalists as well as state and local level policymakers in the areas of agriculture, water management, and emergency drought relief. In assessing possibilities and constraints of forecast application in Ceara, the present analysis takes into account three types of variables: (a) characteristics of the forecasts; (b) policymaking systems; and (c) institutional environments. We conclude that, on the one hand, several factors in the Ceara case have limited the effectiveness of seasonal climate forecast use. First, the current level of skill of the forecasts is inadequate for the needs of policy development and farmer decisionmaking. Second, forecast information application has been subject to distortion, misinterpretation and political manipulation. Third, focus on the forecast as a product until recently neglected to take into account end users' needs and decisionmaking behavior. On the other hand, climate forecasting has the potential to offer a dramatic opportunity for state and local level bureaucracies to embark on a path of proactive drought planning.